2021
DOI: 10.1007/s00167-021-06520-z
|View full text |Cite
|
Sign up to set email alerts
|

Ramp lesions are six times more likely to be observed in the presence of a posterior medial tibial bone bruise in ACL-injured patients

Abstract: Purpose The aim of this study was to determine whether posterior tibial slope (PTS), meniscal slope (MS), and bone bruise pattern (BBP), as observed on magnetic resonance imaging (MRI), differed between patients with or without medial meniscus ramp lesions at the time of anterior cruciate ligament reconstruction (ACLR). The hypothesis was that patients with a ramp lesion had a higher PTS and MS, with a different BBP than patients without a ramp lesion. Methods Fifty-six patients undergoing ACLR were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Furthermore, bone oedema at the posterior MTP and the MFC was also correlated with ramp lesions, and 87.5% of cases with proven ramp lesions had MTP bone oedema, which is in keeping with the same mechanism. This finding is in agreement with previous studies that reported posteromedial tibial bone oedema as an important secondary MRI finding in conjunction with ramp lesions [5,11,27,29]. DePhillipo et al [11] found MTP bone bruises in 72% of their patients diagnosed with ramp lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, bone oedema at the posterior MTP and the MFC was also correlated with ramp lesions, and 87.5% of cases with proven ramp lesions had MTP bone oedema, which is in keeping with the same mechanism. This finding is in agreement with previous studies that reported posteromedial tibial bone oedema as an important secondary MRI finding in conjunction with ramp lesions [5,11,27,29]. DePhillipo et al [11] found MTP bone bruises in 72% of their patients diagnosed with ramp lesions.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the short delay (19.6 ± 15.2 days) from injury to MRI may have prevented the PMT bone bruising to reabsorb and therefore increased its association with meniscal ramp lesions. Most of the literature suggests that PMT bone bruising is an important secondary MRI sign of meniscal ramp lesions [ 3 , 4 , 11 , 20 , 22 , 23 , 41 ]. The strong association between PMT bone bruising and meniscal ramp lesions might be due to one possible common injury mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 23 , 27 As such, various reports have suggested that ramp lesions are 3 to 6 times more likely to be observed when posteromedial tibial plateau (PMTP) bone bruising is present in patients with isolated ACL injuries. 2 , 15 However, there are limited reports of this secondary sign in combined PLC injuries.…”
mentioning
confidence: 99%
“…The Orthopaedic Journal of Sports Medicine, 11 (2), 23259671221144767 DOI: 10.1177/23259671221144767 ª The Author(s) 2023 1 This open-access article is published and distributed under the Creative Commons Attribution -NonCommercial -No Derivatives License (https://creativecommons.org/ licenses/by-nc-nd/4.0/), which permits the noncommercial use, distribution, and reproduction of the article in any medium, provided the original author and source are credited. You may not alter, transform, or build upon this article without the permission of the Author(s).…”
mentioning
confidence: 99%